Flavone-di-C-glycosides in citrus juices from Southern Italy - Caristi, C.; Bellocco, E.; Gargiulli, C.; Toscano, G.; Leuzzi, U.
6,8-Di-C-glucopyranosylapigenin and 6,8-di-C-glucopyranosyldiosmetin were detected by HPLC-DAD-ESI-MS-MS in a variety of Southern Italian Citrus juices (orange, lemon, bergamot, citron, mandarin, clementine). In some juices, the amounts of C-glycosides detected were significant. 6,8-Di-C-glucopyranosylapigenin is characteristic of orange juice, while 6,8-di-C-glucopyranosyldiosmetin is the most important C-glycoside in lemon and citron juice. In bergamot juice the concentrations of 6,8-di-C-glucopyranosylapigenin and 6,8-di-C-glucopyranosyldiosmetin are similar. Clementine juice is distinctive as the amounts of both C-glycosides present are negligible.
Keywords: CITRUS JUICES; FLAVONOIDS; C-GLYCOSIDES; HPLC-DAD-ESI-MS-MS